Rekrutmen Tenaga Pendidik dan Tenaga Kependidikan di SDIT Alam Golden Kota Solok - Nengsih, Dona; Jamilus, Jamilus (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to look at the implementation of recruitment at SDIT Alam Golden, Solok City. Recruitment is the process of obtaining a number of quality human resources to occupy a position or job. Carrying out professional and proportional recruitment will produce quality teaching staff. To examine the implementation of recruitment at SDIT Alam Golden, descriptive qualitative research was used which produces descriptive data in the form of written, spoken words and activities from the people observed. To collect data using interview techniques, observation techniques and documentation techniques. The data analysis procedure used in this research is qualitative analysis. The results of the research obtained the following results: The implementation of recruitment was quite good, here it can be seen that there were various processes carried out by the school, such as through administrative filing and tests for new prospective workers, the expected goals were mostly achieved even though there were still inhibiting factors such as it is difficult to find workers who match their academic fields with the fields needed by the school. However, in this case the school, especially the principal and other workers, are equally trying to ensure that the school remains a school that is popular with the community.